Spectrophotometric color measurement to assess temperature of exposure in cortical and medullar of heated human bones: a preliminary study - Rubio-Lamia, Leticia Olga; Díaz-Vico, Ramona; Smith-Fernández, Inés María; Smith-Fernández, José Aníbal; Suárez-Pérez, Juan; Martín-de-las-Heras, Stella; Santos-Amaya, Ignacio Miguel (My University, 2020)
Heated-bone color changes may provide information about temperature of exposure, with interest for anthropologists and forensic experts. The aim of this study was to assess heat-induced color changes by spectrophotometry in cortical and medullar human bones heated at different temperatures and times. CIELAB (International Commission on Illumination-LAB) color parameters (L*, a*, and b*) and whiteness (WI) and yellowness (YI) indexes were obtained by spectrophotometry in the cortical and medullar zones of 36 bone sections exposed at 200, 400, 600, and 800 °C for 30 and 60 min. The accuracy of color-based temperature estimations was evaluated by Receiver Operating Characteristics (ROC) analysis. Chromaticity a* showed the best significant discrimination power with the area under the ROC curve (AUC) values ranged from 0.9 to 1.0 in cortical zones and 0.7 to 1.0 in medullar zones for all temperatures of exposures and both time of exposures. Chromaticity b*, and WI and YI indexes showed an AUC of 1.0 at 400, 600, and 800 °C for 30 and 60 min in the cortical and medullar zones. The spectrophotometric color parameters provided a highly accurate estimation of the temperature of exposure to discriminate between temperatures and exposure times in the cortical and medullar zones. Spectrophotometric bone color measurement in cortical and medullar zones can be an objective and reproducible method to estimate the temperature of exposition, and it can be considered useful for forensic and anthropological purposes.
Keywords: Huesos; Color measurement; Spectrophotometer; High temperature; Bone